KARAKTERISASI ANATOMI DELIMA (Punica granatum L.) - vivin andriani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
Pomegranate (Punica granatum L) is member of family Punicaeae having etnopharmacological history. In Indonesia, there are three cultivars: red, white and black. Methanol extract of pomegranate have antioxidant activity. This research was intended to identifying its anatomy (stem, leaf, anther, peel and seed). Sample of the three pomegranate cultivars were obtained from the Surabaya agricultural Service. Specimen was made using paraffin shielding method with single staining. The result was descriptive data. The results indicated different anatomic structure on peel of the three cultivars. In exocarp layers black pomegranate has five sclerenchyma layers while red and white pomegranate has four sclerenchyma layers. About stem, leaf, anther and seed, there is no anatomic difference, but there is variation in shape and size. Keywords: Punica granatum L, Anatomy